Neurofibroma of the Sciatic Nerve with Neurofibromatosis Type 1 - Mohammad Ali Naraghi (Acta Medica Iranica, 2011)
"nA 28-year-old man with neurofibromatosis type 1(NF1) presented with a tumor in the sciatic nerve and femoral nerve. The differential diagnosis of malignant peripheral nerve sheath tumor was based on clinical, radiological, and histological evidence. The tumor apparently originated in sciatic nerve at the posterior aspect of the left thigh. The lesion was resected totally without neural damage to the sciatic nerve. The tumor did not recur after 2 years.